Differences and disparities in seasonal influenza vaccine, acceptance, adverse reactions, and coverage by age, sex, gender, and race. Issue 11 (8th March 2022) - Kini, Aniket; Morgan, Rosemary; Kuo, Helen; Shea, Patrick; Shapiro, Janna; Leng, Sean X.; Pekosz, Andrew; Klein, Sabra L.
Highlights: Seasonal influenza vaccine coverage is highest in women, white and older people. Vaccine acceptance is greater in men and white individuals and increases with age. Adverse events are most common in young females. Elderly white men were found to have the best scores across the three parameters. Young women belonging to racial minorities performed the worst. Abstract: Background: Influenza is a significant threat to public health worldwide. Despite the widespread availability of effective and generally safe vaccines, the acceptance and coverage of influenza vaccines are significantly lower than recommended. Sociodemographic variables are known to be potential predictors of differential influenza vaccine uptake and outcomes. Objectives: This review aims to (1) identify how sociodemographic characteristics such as age, sex, gender, and race may influence seasonal influenza vaccine acceptance and coverage; and (2) evaluate the role of these sociodemographic characteristics in differential adverse reactions among vaccinated individuals. Methods: PubMed was used as the database to search for published literature in three thematic areas related to the seasonal influenza vaccine - vaccine acceptance, adverse reactions, and vaccine coverage. Results: A total of 3249 articles published between 2010 and 2020 were screened and reviewed, of which 39 studies were included in this literature review. By the three thematic areas, 17 studies assessed vaccine acceptance, 8 studies focused on adverse reactions, and 14 examined coverage of the seasonal influenza vaccine. There were also two studies that focused on more than one of the areas of interest. Conclusion: Each of the four sociodemographic predictors – age, sex, race, and gender – were found to significantly influence vaccine acceptance, receipt and outcomes in this review.